Isolated growth hormone deficiency in children with vertically transmitted short stature: What do the genes tell us? - Plachy, Lukas; Amaratunga, Shenali Anne; Dusatkova, Petra; Maratova, Klara; Neuman, Vit; Petruzelkova, Lenka; Zemkova, Dana; Obermannova, Barbora; Snajderova, Marta; Kolouskova, Stanislava; Sumnik, Zdenek; Lebl, Jan; et al. (Frontiers in Endocrinology, 2023)
Introduction The growth hormone deficiency (GHD) diagnosis is controversial especially due to low specificity of growth hormone (GH) stimulation tests. It is therefore believed that children diagnosed with GHD form a heterogeneous group with growth disorder frequently independent on GH function. No study evaluating the complex etiology of growth failure in children with diagnosed GHD has been performed thus far. Aims To search for the genetic etiology of growth disorder in children diagnosed as GHD from families with short stature. Methods Fifty-two children diagnosed with primary GHD and vertically transmitted short stature (life-minimum height in both the child and his/her shorter parent <-2 SD) were enrolled to the study. The diagnosis of GHD was based on growth data suggestive of GHD, absence of substantial disproportionality (sitting height to total height ratio <-2 SD or >+2 SD), IGF-1 levels <0 for age and sex specific SD and peak GH concentration <10 ug/L in two stimulation tests. All children were examined using next-generation sequencing methods, and the genetic variants were evaluated using the American College of Medical Genetics guidelines. Results The median age of children at enrollment into the study was 11 years (IQR 9-14 years), their life-minimum height was -3.0 SD (-3.6 to -2.8 SD), IGF-1 concentration prior to GH treatment -1.4 SD (-2.0 to -1.1 SD), and maximal stimulated GH 6.3 ug/L (4.8-7.6 ug/L). None of the children had multiple pituitary hormone deficiency or a midbrain region pathology. Causative variants in genes affecting growth were found in 15/52 (29%) children. Among them, only two (13%) had a variant in a gene involved in the secretion or function of GH (GHSR and OTX2). Interestingly, 10 (67%) patients had a primary defect in the growth plate (ACAN, COL11A1, COL1A2, COL2A1, EXT2, FGFR3, NPR2, NF1, PTPN11 [2x]), one (7%) had a variant in a gene impairing IGF-1 action (IGFALS) and two (12%) had syndromic short stature (MBTPS2, SALL4). Conclusions Genetic findings frequently did not correspond with the clinical diagnosis of GHD in children with vertically transmitted short stature. These results underline the doubtful reliability of standard methods currently used to diagnose GHD.